The Impact of Tuina Massage Therapy on Sensory Processing, Sleep Disturbances, and Maladaptive Behaviors in Young Children with Autism Spectrum Disorder in Jakarta, Indonesia: A Controlled Clinical Study - Fatimah Mursyid; Lin Chia; Khairiel Anwar; Istiqomah Putri; Bjorka Alma (HM Publisher, 2025)
Introduction: Autism spectrum disorder (ASD) is a complex neurodevelopmental condition characterized by challenges in social communication, restricted interests, and repetitive behaviors, often accompanied by sensory processing abnormalities, sleep disturbances, and maladaptive behaviors. Current interventions offer variable efficacy, prompting exploration of complementary therapies. Tuina, a form of therapeutic massage in Traditional Chinese Medicine (TCM), has shown potential in pediatric neurodevelopmental issues. This study aimed to investigate the impact of Tuina massage therapy on sensory processing, sleep quality, and maladaptive behaviors in young children with ASD in Jakarta, Indonesia. Methods: A controlled clinical study was conducted with 88 children aged 3-7 years, diagnosed with ASD according to DSM-5 criteria and confirmed using the Autism Diagnostic Observation Schedule, Second Edition (ADOS-2). Participants were recruited from specialized pediatric clinics in Jakarta and assigned to either an intervention group (n=44) receiving a standardized Tuina protocol thrice weekly for 12 weeks alongside standard care, or a control group (n=44) receiving standard care only. Standard care included established interventions such as behavioral therapy, speech therapy, occupational therapy, or special education programs. Outcome measures included the Sensory Profile 2 (SP-2), the Children's Sleep Habits Questionnaire (CSHQ), and the Aberrant Behavior Checklist-Community (ABC-C), administered at baseline, week 6, week 12 (post-intervention), and at a 3-month follow-up (week 24). Results: At 12 weeks, the Tuina group demonstrated statistically significant improvements compared to the control group in sensory processing, specifically in auditory filtering (mean difference [MD] -8.5, 95% CI -11.2 to -5.8, p<0.001) and tactile sensitivity (MD -7.9, 95% CI -10.5 to -5.3, p<0.001) on SP-2 quadrant scores. Total CSHQ scores indicated significantly better sleep in the Tuina group (MD -6.8, 95% CI -9.1 to -4.5, p<0.001), particularly in subscales of bedtime resistance and sleep anxiety. ABC-C scores for irritability (MD -5.2, 95% CI -7.0 to -3.4, p<0.001) and hyperactivity (MD -6.1, 95% CI -8.3 to -3.9, p<0.001) were also significantly lower in the Tuina group. These improvements were largely maintained at the 3-month follow-up. No serious adverse events were reported. Conclusion: This study provides evidence that Tuina massage therapy, as an adjunct to standard care, can significantly improve sensory processing, reduce sleep disturbances, and mitigate maladaptive behaviors in young children with ASD in an Indonesian context. These findings suggest Tuina may be a valuable complementary intervention for managing core and associated symptoms of ASD. Further research with larger, diverse samples and longer follow-up periods is warranted.